Isolation, structure elucidation, antimicrobial activity and effects of plant extracts used for the treatment of "u wela" - Ramavhale, Tuwani Tryphina (My University, 2024)
Medicinal plants still account for a substantial significant portion of daily medication in South Africa and across the globe. In the Vhembe District, traditional health practitioners and local people use medicinal plants to combat various ailments such as “u wela”, sexually transmitted diseases, diabetes, and tuberculosis in humans. “U wela" also known as “divhu” in “Tshivenda” is a sexually transmitted disease that affects males due to unprotected sexual encounters with a woman who had an abortion or miscarriage. The study aimed to investigate medicinal plants used to treat “u wela” and isolate the active compounds from the most promising plant species. Eight plant species (Elaeodendron transvaalense (Burtt Davy) R. H. Archer, Albizia versicolor Welw. ex Oliv, Xanthocercis zambesiaca Baker, Cassia abbreviata subsp. beareana (Holmes) Brenan, Anthocleista grandiflora Gilg, Myrothamnus flabellifolius Welw. Mimusops zeyheri Sond and Capparis tomentosa Lam.) used to combat “u wela” were selected from the Ethnomedicinal plant's database of over 300 medicinal plants used for medicinal purposes in humans. These plant species are used by the local community and traditional health practitioners in the Vhembe District to combat “u wela”. The plant materials were extracted with solvents of various polarities such as acetone, hexane, methanol, dichloromethane, ethyl-acetate, and water. Methanol extracted a large quantity of plant materials (15.6%), followed by acetone (6.2%), and DCM (0.2%). Thin-layer chromatography (TLC) was used to determine the chemical components of different plant extracts. The TLC plates were developed using different eluent solvent systems such as Benzene: ethanol: ammonia hydroxide (BEA), Chloroform: ethylacetate: formic acid (CEF), and Ethyl-acetate: methanol: water (EMW). The separated compounds were visualised under ultraviolet light at the wavelength of 365 nm and 254 nm before being sprayed with the vanillin-sulphuric acid spray reagent. More compounds were observed in TLC chromatograms separated with BEA (54%), followed by the CEF (33%) and EMW (13%) solvent system, indicating that the majority of compounds were found to be non-polar. Serial dilution assay was used to determine the antifungal activity of the plant extracts against the fungal pathogen, Candida albicans. The plant extracts of A. versicolor, C. abbreviata had excellent activity with a low MIC value ranging between 0.02, and 0.03 mg/ml. Noteworthy, aqueous extracts of E. transvaalense, A. versicolor, X. zambesiaca, M. zeyheri, and C. abbreviata were active against the tested fungal pathogen with MIC values of 0.02 mg/ml. Furthermore, the plant extracts were screened for antibacterial activity against Escherichia coli, Staphylococcus aureus and Neisseria gonorrhoeae. The acetone and methanol extracts of E. transvaalense, X. zambesiaca, C. abbreviata, A. grandiflora, C. tomentosa, M. zeyheri, and M. flabellifolius had excellent activity against the bacterial pathogens with MIC values ranging between 0.02-0.08 mg/ml. In bioautograms developed in BEA, active compounds were visible in the acetone, DCM, and ethyl-acetate extracts of A. versicolor with Rf values of 0.24. A similar active compound was observed in the DCM extract of E. transvaalense with the same Rf value of 0.24 against E. coli. The serial exhaustive extraction method was used to extract plant materials using solvents of different polarities such as hexane, chloroform, acetone, and methanol. The acetone extract was selected based on good antifungal activity against the tested microorganisms and the presence of active compounds was observed in different plant extracts. Column chromatography of the acetone fractions led to the isolation of three compounds. The antimicrobial activity of the isolated compounds was determined against the fungi and bacteria. All compounds were active against the tested microorganisms with MIC values of 0.02-0.08 mg/ml. In bioautography assay, compounds with similar Rf values (0.31) were observed against N. gonorrhoeae. Nuclear Magnetic Resonance (NMR) and Mass Spectrometry (MS) were used for the identification of the isolated compounds. Compound 1 was identified as 10-isopropyl- 4,4-dimethylhexadecahydro-1H-cyclopenta[b]phenanthren-3-ol and compound 2 as a 1-(2,2,5a,9b-tetramethyl-5-vinyldodecahydro-1H-cyclopenta[a]naphthalen-7-yl)ethenone. The cytotoxicity of acetone extracts and isolated compounds were investigated using the (3-(4,5-dimethylthiazol) -2,5-diphenyltetrazoliumbromide) (MTT) assay. The crude extract was less cytotoxic with LC50 = 1.06 mg/ml. Compound 2 was not toxic at the highest concentration with LC50 values greater than 200 μg/ml against the Vero kidney monkey cells. Compound 1 was less toxic towards the Vero cells with LC5 0.179 mg/ml. The study supports the traditional use of the selected plant species to combat “u wela” by the local people and traditional health practitioners
Thesis (Ph.D. (Botany)) -- University of Limpopo, 2024
Keywords: Medicinal plants; Sexually transmitted disease; Antimicrobial activity; Medicinal plants; Sexually transmitted diseases; Plant extracts